Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Dengan Good Corporate Governance Sebagai Variabel Moderasi - Nazwa Hana Faradila; Menik Indrati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of Intellectual Capital on financial performance, proxied by Return on Assets (ROA) and Return on Equity (ROE), with Good Corporate Governance (GCG) as a moderating variable. This study uses 65 samples of banking sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. The research adopts a quantitative approach using secondary data obtained from audited annual financial statements and annual reports. The analysis is conducted using panel data regression with the assistance of EViews 13 software, including the selection of the best model (CEM, FEM, REM) through the Chow test and Hausman test, as well as classical assumption tests and hypothesis testing. The results show that Intellectual Capital has a positive effect on ROA and ROE, indicating that the more optimal the management of a company's intellectual assets—such as knowledge, skills, and innovation—the greater the company's ability to generate profits from both its assets and equity. However, Good Corporate Governance is not able to moderate this relationship, meaning that the implementation of good corporate governance has not been proven to strengthen the effect of Intellectual Capital on financial performance. This suggests that although GCG has been well implemented, its role tends to function more as a monitoring mechanism rather than as a factor that enhances the effectiveness of Intellectual Capital utilization. These findings imply that improvements in banking financial performance are more directly influenced by the optimization of Intellectual Capital rather than through its interaction with GCG. Therefore, companies need to focus more on the strategic management of intellectual resources while maintaining the quality of corporate governance. This study is expected to contribute to managers and investors in understanding the factors influencing the financial performance of banking companies in Indonesia.